Mixed QCD-electroweak corrections to W-boson production in hadron collisions - Behring, A; Buccioni, F; Caola, F; Delto, M; Jaquier, M; Melnikov, K; Röntsch, R (American Physical Society, 2021)
We compute mixed QCD-electroweak corrections to the fully-differential production of an on-shell W boson. Decays of W bosons to lepton pairs are included in the leading order approximation. The required two-loop virtual corrections are computed analytically for arbitrary values of the electroweak gauge boson masses. Analytic results for integrated subtraction terms are obtained within a soft-collinear subtraction scheme optimized to accommodate the structural simplicity of infra-red singularities of mixed QCD-electroweak contributions. Numerical results for mixed corrections to the fiducial cross section of pp→W+→l+ν and selected kinematic distributions in this process are presented.